2010
DOI: 10.1111/j.1574-6941.2009.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of a groundwater bacterial community in the degradation of  the herbicide terbuthylazine

Abstract: A bacterial community in an aquifer contaminated by s-triazines was studied. Groundwater microcosms were treated with terbuthylazine at a concentration of 100 microg L(-1) and degradation of the herbicide was assessed. The bacterial community structure (abundance and phylogenetic composition) and function (carbon production and cell viability) were analysed. The bacterial community was able to degrade the terbuthylazine; in particular, Betaproteobacteria were involved in the herbicide biotransformation. Identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 47 publications
1
31
0
1
Order By: Relevance
“…An unintended consequence of using monensin to inhibit protozoa resulted in enrichment of an uncultured Advenella species known to degrade a chloro- s -triazine herbicide, terbuthylazine, when present in ground water [57]. The enrichment of Advenella, representing one-third of all characterized sequences, indicated that this organism likely used monensin for growth.…”
Section: Discussionmentioning
confidence: 99%
“…An unintended consequence of using monensin to inhibit protozoa resulted in enrichment of an uncultured Advenella species known to degrade a chloro- s -triazine herbicide, terbuthylazine, when present in ground water [57]. The enrichment of Advenella, representing one-third of all characterized sequences, indicated that this organism likely used monensin for growth.…”
Section: Discussionmentioning
confidence: 99%
“…Among s-triazines, terbuthylazine is the most persistent in surface environments (Barra Caracciolo et al, 2010) and, in general, the presence of this herbicide and its metabolites DET and HT occurs at the same time, with their concentrations commonly being higher than those of the parent compound.…”
Section: Alt-s1mentioning
confidence: 99%
“…linuron in case of L SM A, and linuron and MCPA/2,4-D in case of BPS Kortrijk. Atrazine has been banned for use since many years but atzA can be linked to terbuthylzamine, another triazine compound with structure highly similar to atrazine, present in the wastewater (Caracciolo et al, 2010). Several other catabolic gene functions were recovered, including amidohydrolases and dioxygenases, which are likely involved in, but could not be directly linked to the degradation of a particular xenobiotic substrates.…”
Section: Lr-pcr To Recover Accessory Regions Of Is1071 Composite Tranmentioning
confidence: 99%